Penapisan Fitokimia dan Penetapan Kadar Polifenol Total Ekstrak Etanol 70% Teh Putih (Camellia sinensis L.) - Nurul Siti Aisyah; Sani Ega Priani; Gita Cahya Eka Darma (UNISBA Press, 2024)
Abstract. White tea contains many secondary metabolites with the highest secondary metabolite compound being polyphenols. Phytochemical screening was done on alkaloid, flavonoid, polyphenol, tannin, saponin, steroid & triterpenoid, monoterpenoid & sesquiterpenoid, and anthraquinone compounds. Extraction of white tea was carried out by reflux method using 70% ethanol. The total polyphenol content contained in 70% ethanol extract of white tea was measured using the Folin-Ciocalteu method. The results showed that 70% ethanol extract of white tea contained secondary metabolites of alkaloid compounds, flavonoids, polyphenols, tannins, saponins, steroids & triterpenoids, and monoterpenoids & sesquiterpenoids. And has a total polyphenol content of 330,920 ± 4,98 mgGAE/gram or 33,092%. Abstrak. Teh putih diketahui mengandung banyak metabolit sekunder dengan senyawa metabolit sekunder paling tinggi yaitu polifenol. Penapisan fitokimia dilakukan terhadap golongan senyawa alkaloid, flavonoid, polifenol, tannin, saponin, steroid & triterpenoid, monoterpenoid & seskuiterpenoid, dan antrakuinon. Ekstraksi teh putih dilakukan dengan metode refluks menggunakan etanol 70%. Kemudian kadar polifenol total yang terkandung dalam ekstrak 70% etanol teh putih diukur menggunakan metode Folin-Ciocalteu. Hasil penelitian menunjukan ekstrak etanol 70% teh putih mengandung metabolit sekunder senyawa alkaloid, flavonoid, polifenol, tannin, saponin, steroid & triterpenoid, dan monoterpenoid & seskuiterpenoid. Serta memiliki kadar polifenol total sebesar 330,920 ± 4,98 mgGAE/gram atau sebesar 33,092%.